Pengaruh Penerapan E-Filing dan Transparansi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Beauty Rosemarry Puteri Augustine Makmur; Elly Halimatusadiah (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Tax is one of the sources of state revenue for government and development costs. The purpose of this study is to determine the effect of e-filing implementation on individual taxpayer compliance, to determine the effect of tax transparency on individual taxpayer compliance, to determine the effect of e-filing implementation on individual taxpayer compliance moderated by tax knowledge, to determine the effect of tax transparency on individual taxpayer compliance moderated by tax knowledge. This study uses descriptive and verification methods with a quantitative approach. The sampling technique uses a non-probability sampling technique using the incidental sampling method. The sample used in this study was 108 individual taxpayers registered at the Bandung Cibeunying Pratama Tax Office. Hypothesis testing used in this study uses Partial Least Square (PLS) using SmartPLS 4 tools or software. Based on the results of the tests conducted, the results of the study indicate that the implementation of e-filing has a significant positive effect on individual taxpayer compliance, tax transparency has a significant positive effect on individual taxpayer compliance, tax knowledge cannot moderate the effect of e-filing implementation on individual taxpayers, tax knowledge cannot moderate the effect of tax transparency on individual taxpayer compliance. Abstrak. Pajak merupakan salah satu sumber penerimaan negara untuk biaya penyelenggaraan pemerintah dan pembangunan. Tujuan dari penelitian ini untuk mengetahui pengaruh penerapan e-filing terhadap kepatuhan wajib pajak orang pribadi, pengaruh transparansi pajak terhadap kepatuhan wajib pajak orang pribadi, pengaruh penerapan e-filing terhadap kepatuhan wajib pajak orang pribadi yang dimoderasi oleh pengetahuan perpajakan, serta pengaruh transparansi pajak terhadap kepatuhan wajib pajak orang pribadi yang dimoderasi oleh pengetahuan perpajakan. Penelitian ini menggunakan metode deskriptif dan verifikatif dengan pendekatan kuantitatif. Teknik pengambilan sampel menggunakan non probability sampling dengan metode incidental sampling. Sampel yang digunakan sebanyak 108 wajib pajak orang pribadi yang terdaftar di KPP Pratama Bandung Cibeunying. Pengujian hipotesis menggunakan Partial Least Square (PLS) dengan bantuan software SmartPLS 4. Berdasarkan hasil pengujian, penerapan e-filing dan transparansi pajak berpengaruh positif signifikan terhadap kepatuhan wajib pajak orang pribadi. Namun, pengetahuan perpajakan tidak dapat memoderasi pengaruh penerapan e-filing maupun transparansi pajak terhadap kepatuhan wajib pajak orang pribadi.